Knowledge of orthodontic tooth movement through the maxillary sinus: a systematic review - Wentian Sun; Kai Xia; Xinqi Huang; Xiao Cen; Qing Liu; Jun Liu (BMC, 2018)
Abstract Background To investigate the feasibility, safety and stability of current interventions for moving teeth through the maxillary sinus (MTTMS) by performing a systematic review of the literature. Methods The electronic databases PubMed, Embase, CENTRAL, Web of Science, CBM, CNKI and SIGLE were searched without a language restriction. The primary outcomes were parameters related to orthodontic treatment, including orthodontic protocols, magnitude of forces, type of tooth movement, duration and rate of tooth movement, and remolding of alveolar bone and the maxillary sinus floor. The secondary outcomes were safety and stability, including root resorption, perforation of the sinus floor, loss of pulp vitality and periodontal health and relapse. Results Nine case reports with 25 teeth were included and systematically analyzed. Fifty to two hundred g of force was applied to move teeth through the maxillary sinus. Bodily movement was accomplished, but initial tipping was observed in 7 cases. The rate was 0.6-0.7 mm/month for molar intrusion and 0.16-1.17 and 0.05-0.16 mm/month for mesial-distal movement of premolars and molars, respectively. Bone formation and remolding of the sinus floor occurred in 7 cases. Root resorption within 6 to 30 months was observed in 3 cases, while no cases of perforation of the sinus floor, loss of pulp vitality, periodontal health impairment or relapse were reported. Conclusions At the present stage, no evidence-based protocol could be recommended to guide MTTMS. The empirical application of constant and light to moderate forces (by TAD, segment and multibrackets) to slowly move teeth through or into the maxillary sinus in adults appears to be practical and secure. Bodily movement was accomplished, but teeth appear to be easily tipped initially, potentially resulting in root resorption. However, this conclusion should be interpreted with caution as the currently available evidence is based on only a few case reports or case series and longitudinal or controlled studies are lacking in this area.